Revealing the effect of local-based teaching materials toward scientific reasoning, argumentation, and problem-solving in biology classroom - Maisuna Kundariati; Lailatul Maghfiroh; Sri Endah Indriwati; Fatchur Rohman; Bagus Priambodo (University of Muhammadiyah Malang, 2022)
Scientific reasoning, argumentation, and problem-solving are essential skills in 21st century. They help people solve problems in daily life. This study aimed to investigate the effect of local-based teaching materials on student’s argumentation, scientific reasoning, and problem-solving skills using Science Project-based Learning (SPjBL). Argumentation skill is a social and dynamic process, involving individuals engaged in thinking, constructing, and critiquing knowledge in science. Scientific Reasoning skills require students to give reasons in the form of opinion or actions and conclusions by using appropriate language to explain what they think and making judgments or decisions based on the produced reasons or evidence. Problem-Solving skill is a process of designing, evaluating, and implementing a strategy to answer questions. In this study, the time series approach was used as a part of the quasi-experimental design with Science Project-based Learning (SPjBL) as the learning model. A total of 29 Biology students of Universitas Negeri Malang participated in this study in August-November 2019 at the Department of Biology of the university. The data was collected using pre-test and post-test instruments which measured scientific argumentation, scientific reasoning, and Problem-solving skill variables. The data analysis was done using ANCOVA test in SPSS 16.0. The results of this study show that there is positive effects of local-based invertebrate and vertebrate materials on scientific argumentation, scientific reasoning, and problem-solving skills. These findings can be used as reference for educator to gain students’ scientific reasoning, argumentation, and problem-solving skills in science classroom through Science Project-based Learning (SPjBL) with the help of local-based teaching materials.